Development Of Flipped Classroom Learning Videos as a Source of Independent Knowledge Exploration - Aristin, Nevy Farista; Hastuti, Karunia Puji; Apriati, Yuli; Rixal, Rixal; Wahyuni, Sri (Universitas Lambung Mangkurat, 2024)
With technological advances in education, the flipped classroom model is a potential learning model in the use of digital technology that involves students exploring knowledge independently. The classroom environment becomes an interactive and quality environment as a place to strengthen the material. So, it is necessary to develop learning media in the form of flipped classroom learning videos to improve the quality of the learning process. This research aims to develop flipped classroom learning videos as a source of independent knowledge exploration. Development research using the ADDIE model is limited to the development stage. Validation tests are carried out by competent educational practitioners in learning and R&D, namely media experts. Data analysis is used in this research by calculating the weight for each aspect or group of aspects assessed. The results of this development research are in the form of flipped classroom learning video products declared very suitable for use. With this video, educators and educational practitioners can clearly understand the syntax of flipped classroom learning. This flipped classroom learning video has implications for teachers, lecturers, and educational practitioners in using the flipped classroom model in their learning process to achieve learning goals.